Enamel defect of primary dentition in SGA children in relation to onset time of intrauterine growth disturbance - Sjarif, Willyanti Soewondo (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Prenatal disturbances disturb the development of organs resulting in small for gestational age (SGA) babies and also causes enamel defects in primary teeth. There are disturbances occur in the beginning of pregnancy causing symmetrical SGA, and asymmetrical type of SGA, where the disturbances occur late in pregnancy. Purpose: This research was to determined differences in severity of enamel defect of primary dentition in small for gestational age children based on the time of intrauterine growth restriction. Methods: This was a clinical epidemiological cohort study. The Ponderal index was used to determine SGA type. The subjects were 129 SGA children aged 9-42 months, 82 with asymmetrical SGA and 47 with symmetrical SGA. Two hundred normal birth weight children were the control group. Intra-oral examinations to determine enamel defect used the FDI modification of the Developmental Defect of Enamel score at 3 months intervals. Statistical t-tests were used to test the difference in severity of enamel defect, and chisquare to find out the difference of Relative Risk Ratio (RRR). Results: The results showed that the enamel defect scores of symmetrical SGA were significantly higher than those with asymmetrical SGA. RRR for severe defect was also significantly higher in symmetrical type for anterior and canines. Conclusion: The study suggested that the severity of enamel defect for infants with symmetrical SGA was higher than those with asymmetrical SGA, indicating that the severity of the defect occurs in the beginning of pregnancy is more severe than in the late pregnancy. Latar belakang: Adanya gangguan prenatal mengganggu perkembangan organ, mengakibatkan terjadinya bayi lahir dengan kecil masa kehamilan (KMK) dan defek email pada gigi sulung. Terdapat 2 tipe KMK yaitu tipe simetri; gangguan terjadi pada awal kehamilan; dimana lingkar kepala, berat dan panjang lahir lebih rendah dari normal. Tipe asimetri dimana gangguan terjadi saat kehamilan lanjut: panjang dan berat badan lahir lebih rendah dari normal. Tujuan: Penelitian ini bertujuan meneliti perbedaan keparahan defek email gigi sulung pada anak KMK berdasarkan saat terjadinya gangguan hambatan pertumbuhan intrauterin. Metode: Jenis penelitian adalah epidemiologi dengan studi Kohort. Ponderal indeks digunakan untuk menentukan tipe KMK subjek terdiri dari anak KMK usia 9-42 bulan, 82 tipe asimetri dan 47 tipe simetri, 200 anak dengan berat lahir normal sebagai kontrol. Pemeriksaan intra oral dilakukan untuk menentukan skor defek email yaitu dengan menggunakan skoring modifikasi DDE indek dari FDI. Subjek di teliti dengan interval 3 bulan, t-test digunakan untuk menentukan perbedaan defek email pada KMK simetri dan asimetri sedangkan chi square menentukan perbedaan RRR (Rasio Resiko Relatif). Hasil: Hasil menunjukan bahwa skor defek enamel pada KMK simeteri lebih tinggi secara signifikan dibanding pada KMK asimetri dan RRR pada defek berat lebih tinggi pada KMK simetri pada gigi anterior dan kaninus. Simpulan: Penelitian ini menunjukkan bahwa defek email lebih parah bila terjadi pada awal masa kehamilan (tipe simetri) dibanding bila terjadi pada saat kehamilan lanjut (tipe asimetri).<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />